(NkRIMINALISTIKA (B:s (Nu^EBNOE POSOBIE (B/s - (NaLENI^EW(B, (Np(B.(Nn(B.s; (NbELKIN(B, (NrAFAIL sAMUILOWI^s; (NbELKIN(B, (Nr(B.(Ns(B.s ((NmOSKWA (B:s (N`RID(B. (NLIT(B.,s, 1986)
(NaLF(B.-(NPREDM(B. (NUKAZ(B.: (NS(B. 538-541s
(NaWT(B. (NUKAZANY NA OBOROTE TIT(B. (NL(B.s
Keywords: (NkRIMINALISTIKAs